Collaboration: The Paradigm of Practice Approach between the Forensic Psychiatrist and the Forensic Psychologist - Gbadebo-Goyea, Ernest A.; Akpudo, Hilary; Jackson, Cynthia D.; Wassef, Tamer; Barker, Narviar C.; Cunningham-Burley, Rhonda; Ali, Shahid; Jabeen, Shagufta; Bailey, Rahn K. (Frontiers in Psychiatry, 2012)
The importance and relevance of forensic practice to societal evolution has increased exponentially in recent years. As society evolves in its understanding of the complex relationships between mankind and society, we rely more and more on the services of forensic experts. This article elucidates the professions of forensic psychiatry and forensic psychology. We look at the two distinct professions from the spectrum of collaboration, integration of services, differences and similarities. Furthermore, we compare and contrast the educational background and training requirements for the two professions. We present illustrative scenarios and real life examples of the daily functions of both professionals. Finally, we present demographic data for the areas of employment, number and geographic distribution of the two professions. Forensic psychiatry is the interface between medicine and law, while forensic psychology is the interface between psychology and law. As such, these professions are mired with complexities and challenged by vulnerabilities. Professionals from both fields can serve as expert witnesses in court and therefore face similar challenges in their course of professional practice. Collaboration between these two professions has the potential to increase both the credibility and utility of forensic services to the courts, the individuals served, and the general public